2018
DOI: 10.1371/journal.pone.0209164
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum levels of intraoperative brain natriuretic peptide for predicting acute kidney injury in living donor liver transplantation

Abstract: BackgroundPatients with end-stage liver disease frequently experience acute kidney injury (AKI) after living donor liver transplantation (LDLT). Serum levels of brain natriuretic peptide (BNP) have increasingly been accepted as a predictor of AKI in clinical settings. This study investigated the predictive role of intraoperative BNP levels in the early development of AKI after LDLT.Patients and methodsAdult patients (≥19 years old) who had undergone elective LDLT from January 2011 to December 2017 were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…However, we adopted the 2012 KIDIGO definition of AKI in our study, which is still based on increases in serum creatinine concentrations. New biomarkers of kidney injury, such as serum cystatin C (ScysC) Neutrophil Gelatinase-Associated Lipocalin (NGAL) and brain natriuretic peptide (BNP) may facilitate earlier detection of renal injury, and thus early intervention aimed at limiting the associated morbidity and mortality [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we adopted the 2012 KIDIGO definition of AKI in our study, which is still based on increases in serum creatinine concentrations. New biomarkers of kidney injury, such as serum cystatin C (ScysC) Neutrophil Gelatinase-Associated Lipocalin (NGAL) and brain natriuretic peptide (BNP) may facilitate earlier detection of renal injury, and thus early intervention aimed at limiting the associated morbidity and mortality [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a close correlation between serum levels of BNP and diastolic parameters on echocardiography, such as tissue Doppler imaging, is present so that high serum levels of BNP (> 100 pg/mL) are reflected by increased left ventricular filling pressure [38,39]. In previous LT studies, high serum levels of BNP were significantly associated with poor postoperative outcomes, such as graft dysfunction, kidney injury, and patient survival [24,29,40]. In our study, patients with normal diastolic function experienced a significant decrease in the proportion of high BNP level (> 100 pg/mL) through the surgical phases; however, this finding was not evident in the patients with diastolic dysfunction according to both recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…According to our hospital LDLT protocol that was described previously in detail [24,25], the piggyback surgical procedure was applied using the right lobe from the living donor that was larger than 40% of the recipient’s standard liver volume or 0.8% of the recipient’s body weight [26]. After completing the hepatic vascular anastomosis, intact hepatic circulation was demonstrated using Doppler ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found elevated concentrations of B-type natriuretic peptide (BNP) or N-terminal pro-B-type natriuretic peptide (NT-proBNP) in patients with ACS and have a prognostic value in patients with ACS [ 18 , 19 ]. Moreover, some studies have found that levels of BNP or NT-proBNP are higher in patients with AKI [ 20 22 ], especially for those who are diagnosed with ACS and undergo coronary angiography or PCI [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%